Food for thought: interpreting the parable of the loyal and wise slave in Q 12:42-44 - L. Howes (Acta Theologica)
The parable of the loyal and wise slave appears in Q 12:42-46 (Matt. 24:45-51; Luke 12:42-46). I have argued elsewhere that verses 45-46 were added to verses 42-44 by Q’s main redactor. If so, only Q 12:42-44 originally appeared in Kloppenborg’s formative stratum, or Q1. The purpose of the present article is to ascertain the parable’s meaning as it seemingly appeared on the level of Q’s formative stratum. The latter is mainly achieved by taking seriously the parable’s application of the slavery metaphor. It should not come as a surprise that the parable in Q 12:42-44 is all about feeding God’s people.